Local governments in EU countries: competences and financing of public services - Halásková, Renáta; Halásková, Martina (Univerzita Pardubice, 2017)
Local governments in the EU play a major role in the development of local public policies. Local governments provide public services in the public interest, funding them for public resources. The paper deals with the role of the local public sector and the comparison of competences of sub-national governments (local, intermediate, regional) in EU countries and the financial dimension of local and regional governments for development of services. The areas assessed include spending capabilities of local governments in 28 EU countries, with a particular focus on total expenditures of local and regional governments, fiscal decentralisation of expenditures, and local government expenditures by selected function (social protection, health, education, culture and recreation), including the rate of their decentralisation of expenditures. The empirical research renders a comparison of spending capabilities of local and regional governments by selected function in EU countries, making use of cluster analysis and the evaluation of similarities and differences in the individual countries. The most marked differences in EU countries were observed in expenditures of the local public sector on health. Conversely, the least marked differences in all countries are seen in the expenditures of the local public sector on recreation and culture.
Keywords: local governments; public services; government expenditure; fiscal decentralisation; cluster analysis; EU countries; H75; H76; H83